Need Assessment For Developing An Online English Proficiency Test Instrument In Higher Education During Covid-19 Pandemic - Asa Bani Putria; Wahyu Lestari (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2020)
This study aims to find out things needed to develop an online English proficiency test instrument in higher education during COVID-19 pandemic. The method of this study was descriptive qualitative method by using observation and interview as the data collection techniques. This study mention three main points that are needed in developing an online test instrument. The first is the system or application that will be used in conducting the online test. The second is the administrator of the online test. The last point is the device and facilities that support the online test.